Analysis of Results of Test Resistance Isolation Power Transformator Based on Polarization Index Test and Delta Tanngen - Mulyana, Elih; Hasbullah, Hasbullah; Sayefullah, Dzikri (Universitas Pendidikan Indonesia, 2020)
The transformer is the leading equipment in the electric power system that is directly related to the electrical transmission and distribution system. An essential part of a power transformer is its insulation system. Along with age and its operation, the condition of insulation can be damaged, which can lead to failure of the surgery. The purpose of this study was to determine the quality conditions of the power transformer insulation. The method in this research is observation and study of literature, while the research location is PT PLN (Persero) TJBT APP Cirebon. Data were taken in the form of polarization index and delta tangent test results. After the data is collected, the polarization index and delta tangent are calculated and analyzed. Analysis of the polarization index testing using the primary-ground, secondary-ground, tertiary-ground, primary-secondary, secondary-tertiary, and primary-tertiary methods. Whereas tangent delta testing is the relationship between CH, CHL, CL, CT, CHT, and CLT.The results of tests with delta polarization and tangent indexes that the transformer isolation resistance is still good and the transformer is feasible to operate.